Impact of Folic Acid in Modulating Antioxidant Activity, Osmoprotectants, Anatomical Responses, and Photosynthetic Efficiency of Plectranthus amboinicus Under Salinity Conditions - Al-Elwany, Omar A. A. I.; Hemida, Khaulood A.; Abdel-Razek, Mohamed A.; El-Mageed, Taia A. Abd; El-Saadony, Mohamed T.; AbuQamar, Synan F.; El-Tarabily, Khaled A.; Taha, Ragab S. (Frontiers in Plant Science, 2022)
Salinity is a major threat to the sustainability of agricultural production systems. Salt stress has unfavorable implications on various plant physio-morphological and biochemical reactions, causing osmotic and ionic stress. Exogenously-applied folic acid (FA) may at least provide one mechanism to evade the injurious stress effects of saline irrigation water on Plectranthus amboinicus (Lour.) Spreng. In this regard, two pot trials were performed during the 2018–2019 and 2019–2020 seasons in an open greenhouse of the experimental farm (29°17'N; 30°53'E) in Fayoum, Egypt. We tested four levels of saline irrigation water (SW): (34, 68, and 102 mM NaCl, plus tap water as the control = 0), combined with FA at three concentrations (25, and 50 μM, plus spray with distilled water as the control = 0). The growth parameters, biochemistry, physiology, elemental leaf status, essential oil content, and anatomical responses were assessed. Salt markedly reduced photosynthetic productivity (Fv/Fm and performance index (PI)), total chlorophyll (SPAD), and leaf osmoprotectant compounds; i.e., total soluble sugar (TSS), free amino acids, proline, and total phenolics, thus hampering P. amboinicus growth and essential oil yield. However, addition of FA as foliar spray to P. amboinicus irrigated with saline water induced increases in Fv/Fm, SPAD and PI. These were linked with enriched stem anatomical structures, leaf osmoprotectant compounds, and enhanced leaf enzymatic activity, e.g., superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR), glutathione (GSH), and ascorbate (ASA) and antioxidant content. Under salt stress, supplementation of 25 and 50 µM FA increased growth and production of essential oil by 27.8% and 55.6%, respectively, compared with no applied FA. The highest growth characteristics and elemental leaf contents were obtained when P. amboinicus was irrigated with 0.0 mM saline water and treated foliarly with 50 µM of FA compared with non-treated plants. Overall, these data show that foliar spraying FA improves efficiency for reducing salt stress impacts on P. amboinicus irrigated with saline water.